The clinical impact of endoscopic ultrasound-guided fine-needle aspiration on the patients with low-risk pancreatic cystic lesions - Pan, Shubo; Liu, Jie; Guo, Jiefang; Zhu, Qilin; Wang, Liangjing; Shi, Xiaohua (Frontiers in Oncology, 2022)
Background and aims. Endoscopic ultrasound (EUS) is playing a more and more important role in the management of pancreatic cystic lesion (PCLs). The aim of our study was to evaluate the clinical impact of EUS and EUS guided fine needle aspiration (FNA) on patients with low-risk PCLs. Materials and methods. Low-risk PCL patients who underwent EUS-FNA in 2 edoscopic centers were retrospectively collected and analyzed. The clinical impact of EUS-FNA on these patients was analyzed and the predictors for significance EUS-FNA (defined by diagnosis and treatment method change, new high-risk feature identified after imaging scans) were analyzed by logistic regression analyses. Results.From July 2004 to February 2017, 186 patients with low-risk PCLs were included. The study cohort had a mean age of 52.4±15.9 years (range: 19-86 years) with 89 (47.8%) male patients included. The clinical significance of EUS-FNAs was observed in 74 patients (39.8%). The presumed diagnoses of PCLs by imaging were changed in 51 (51/74, 68.9%) patients. Nineteen (19/74, 25.7%) new high-risk features were identified by EUS-FNA, and four patients (4/74, 5.4%) underwent surgery due to suspicious or malignant cytology. Based on multivariate analysis, large cyst size [odds ratio (OR): 1.12, 95% confidence interval (CI): 1.02–1.19, P = 0.033], young age (OR: 0.94, 95% CI: 0.91–0.99, P = 0.041) and BMI over 25 (OR: 3.15, 95% CI: 1.29–7.86, P = 0.013) were independent predictors of clinical significance for EUS-FNA. The optimal age and cyst size to predict significance EUS-FNA was 46.0 years and 2.3cm. Conclusions. On the basis of a 2-center retrospective study, EUS-FNA was clinically significant in about 40% of low-risk PCLs, especially in young, large cyst size, and overweight patients.